2008
DOI: 10.1002/elps.200700140
|View full text |Cite
|
Sign up to set email alerts
|

Separation and determination of flavonoids using microemulsion EKC with electrochemical detection

Abstract: A selective and sensitive method of microemulsion EKC (MEEKC) with electrochemical detection (ED) was developed for separation and determination of 14 flavonoids. In order to obtain the better stability for the studied flavonoids, oil (ethyl acetate) with low interfacial surface tension was employed as organic solvent. A running buffer composed of 0.9% (w/v, 30 mM) SDS, 0.9% (w/v, 21 mM) sodium cholate (SC), 0.9% (w/v, 121 mM) butan-1-ol, 0.6% (w/v, 68 mM) ethyl acetate, and 98.2% v/v 10 mM Na(2)B(4)O(7)-20 mM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…In order to improve the sensitivity, some sensitive detectors, such as laser-induced fluorescence and MS [29][30], can be used to improve the sensitivity for several orders, but they are not widely applicable due to their expensive cost for common user. We have proposed an MEEKC electrochemical detection method for separation and determination of flavonoids [31]. However, treatment of the microelectrode was time-consuming and tedious.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the sensitivity, some sensitive detectors, such as laser-induced fluorescence and MS [29][30], can be used to improve the sensitivity for several orders, but they are not widely applicable due to their expensive cost for common user. We have proposed an MEEKC electrochemical detection method for separation and determination of flavonoids [31]. However, treatment of the microelectrode was time-consuming and tedious.…”
Section: Introductionmentioning
confidence: 99%
“…Improved LODs have also been achieved through use of LIF [69] and electrochemical detection [70]. Yu et al [70] achieved the separation of 14 flavanoids using MEEKC and reported detection limits ranging from 0.02 to 0.5 mg/L with electrochemical detection.…”
Section: Improved Lodsmentioning
confidence: 99%
“…Yu et al [70] achieved the separation of 14 flavanoids using MEEKC and reported detection limits ranging from 0.02 to 0.5 mg/L with electrochemical detection.…”
Section: Improved Lodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These properties are mainly correlated to their antioxidant activity, such as anticancer, antiviral, anti-inflammatory, effects on capillary fragility, and their ability to inhibit human platelet aggregation [2,3]. Various methods have been developed for the separation and detection of flavonoids in medicinal plants, such as polyamide chromatography, gas chromatography (GC) [4,5], high performance liquid chromatography-mass spectrometry (HPLC-MS) [6][7][8], capillary electrophoresis (CE) [9][10][11][12], micellar electrokinetic capillary chromatography (MECC) [13][14][15][16] and microemulsion electrokinetic chromatography (MEEKC) [17]. To the best of our knowledge, there are few reports about the separation and determination of flavonoids by capillary electrochromatography (CEC) using methacrylate ester-based monolithic columns [3,18].…”
Section: Introductionmentioning
confidence: 99%